Pendukung Peningkatan Profesionalitas Guru Raudlatul Athfal - M Agung Hidayatulloh (STIT Al-Marhalah Al-Ulya Bekasi, 2019)
This work pays attention to the supporting factors of professional improvement of Islamic kindergarten teachers. With a descriptive qualitative method, this research shows that the improvement of professionalism was supported by the internal factors as work enthusiasm, character, and loyalty. Whereas the supports of colleagues, families, government notices, and profession demand, thoughtfulness to the environment, and the spirit of educating children became external factors supporting the efforts.Â